2003
DOI: 10.1074/jbc.m204243200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Thioguanine-modified Duplex DNA

Abstract: Mercaptopurine and thioguanine, two of the most widely used antileukemic agents, exert their cytotoxic, therapeutic effects by being incorporated into DNA as deoxy-6-thioguanosine. However, the molecular mechanism(s) by which incorporation of these thiopurines into DNA translates into cytotoxicity is unknown. The solution structure of thioguanine-modified duplex DNA presented here shows that the effects of the modification on DNA structure were subtle and localized to the modified base pair. Specifically, thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
70
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 39 publications
8
70
0
Order By: Relevance
“…Therefore, changes in chromatin architecture or gene regulation patterns could be important determinants of antimetabolite therapy. Structural analysis of synthetic DNA showed that incorporation of nucleoside analogs into DNA does not introduce gross changes in DNA geometry (Sahasrabudhe et al, 1996;Somerville et al, 2003). Instead, drastic shifts in DNA dynamics occur; for example, incorporation of deoxythioguanosine makes DNA more flexible (Somerville et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, changes in chromatin architecture or gene regulation patterns could be important determinants of antimetabolite therapy. Structural analysis of synthetic DNA showed that incorporation of nucleoside analogs into DNA does not introduce gross changes in DNA geometry (Sahasrabudhe et al, 1996;Somerville et al, 2003). Instead, drastic shifts in DNA dynamics occur; for example, incorporation of deoxythioguanosine makes DNA more flexible (Somerville et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several antimetabolite agents do not disrupt integrity of DNA and lead only to minute alterations in DNA geometry (Sahasrabudhe et al, 1996;Somerville et al, 2003). Instead, incorporation of these chemical moieties into DNA increases local flexibility of the double helix in the area surrounding the modification, and changes the DNA-protein interactions (Krynetskaia et al, 2000;Somerville et al, 2003;Seibert et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, 2 0 -deoxy-6-thioguanosine-5 0 triphosphate (dG S TP) is incorporated into DNA, subsequently showing a characteristic delayed cytotoxic effect (Maybaum and Mandel, 1983). Recent studies have shown that the incorporation of dG s TP into duplex DNA results in subtle localised modification on DNA structure (Somerville et al, 2003). Moreover, chromatin structure alteration is most evident in the G2 phase of the cell cycle (Maybaum and Mandel, 1983).…”
mentioning
confidence: 99%
“…[1][2][3] Thioguanine, which is used in the therapy of acute leukemia, is believed to exert its cytotoxic therapeutic effect by being incorporated into DNA as deoxy-6-thioguanosine. [4,5] Because of their therapeutic relevance, these modified bases have also been the subject of theoretical studies. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%